一种基于在线修正的桥式振弦应变计 (2024)
本发明公开了一种基于在线修正的桥式振弦应变计，第一振弦固定于第一、第二固定端之间，第二振弦固定于第二、第三固定端之间，第三振弦固定于第四、第五固定端之间，第四振弦固定于第五、第六固定端之间，第一振弦上设置可引发激振的第一激振电磁线圈，第二振弦上设置可引发激振的第二激振电磁线圈，第三振弦上设置可引发激振的第三激振电磁线圈，第四振弦上设置可引发激振的第四激振电磁线圈，检测仪器分别与第一、第二、第三及第四激振电磁线圈相连接，第一与第二电磁线圈串联、第三与第四电磁线圈串联，这两部分串联结构组成并联结构，四部分激振电磁线圈为对称关系，可有效提高应变计灵敏性、精度、抗干扰能力及测量数据有效性。 The invention discloses an on-line correction-based bridge-type vibrating string extensometer. A first vibration string is fixedly arranged between a first fixed end and a second fixed end, a second vibration string is fixedly arranged between the second fixed end and a third fixed end, a third vibration string is fixedly arranged between a fourth fixed end and a fifth fixed end, a fourth vibration string is fixedly arranged between the fifth fixed end and a sixth fixed end, a first excitation solenoid coil is arranged on the first vibration string and can be used for triggering excitation, asecond excitation solenoid coil is arranged on the second vibration string and can be used for triggering excitation, a third exci